2008
DOI: 10.4049/jimmunol.180.9.6346
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Secretion Depends on Galα(1,3)Gal Expression in a Pig-to-Human Whole Blood Model

Abstract: Transplants from α1,3-galactosyltransferase (Gal) gene-knockout pigs to nonhuman primates are largely protected from hyperacute but not acute humoral xenograft rejection. The present study investigates the role of Gal in cytokine responses using a novel pig-to-human whole blood in vitro model, developed for species-specific analysis of porcine and human cytokines. Porcine (n = 7) and human (n = 27) cytokines were measured using ELISA or multiplex technology, respectively. Porcine aortic endothelial cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Analyzing in vitro lymphocyte proliferation induced by wild-type or GalT-KO endothelial cell shows that aGal epitope expression on the endothelium is associated with a greater proliferation of CD4 þ and CD8 þ T cells (Lin et al 2008;Wilhite et al 2012), suggesting an as-yetunidentified role of aGal epitopes in sustaining T cell response. The absence of aGal is also associated with a significantly reduced secretion of INF-g, TNF-a, IL-17A by CD4 þ T cells, and of INF-g, granzyme-B, and the chemokine IP-10 by CD8 þ T cells (Wilhite et al 2012), partially confirming earlier findings reported by Saethre et al (2008), who showed that exposure to Gal þ/þ endothelial cells was associated with a significant release of human INF-g, human and porcine proinflammatory IL-6 and IL-8, and several human b chemokines, whereas this picture was not seen after exposure to Gal 2/2 cells (Saethre et al 2008). Unlike the report from Wilhite et al (2012), however, the T-cell-recruiting a-chemokine IP-10 in the Saethre study was induced in cells lacking the aGal epitopes.…”
Section: Cell-mediated Xenograft Rejectionsupporting
confidence: 88%
“…Analyzing in vitro lymphocyte proliferation induced by wild-type or GalT-KO endothelial cell shows that aGal epitope expression on the endothelium is associated with a greater proliferation of CD4 þ and CD8 þ T cells (Lin et al 2008;Wilhite et al 2012), suggesting an as-yetunidentified role of aGal epitopes in sustaining T cell response. The absence of aGal is also associated with a significantly reduced secretion of INF-g, TNF-a, IL-17A by CD4 þ T cells, and of INF-g, granzyme-B, and the chemokine IP-10 by CD8 þ T cells (Wilhite et al 2012), partially confirming earlier findings reported by Saethre et al (2008), who showed that exposure to Gal þ/þ endothelial cells was associated with a significant release of human INF-g, human and porcine proinflammatory IL-6 and IL-8, and several human b chemokines, whereas this picture was not seen after exposure to Gal 2/2 cells (Saethre et al 2008). Unlike the report from Wilhite et al (2012), however, the T-cell-recruiting a-chemokine IP-10 in the Saethre study was induced in cells lacking the aGal epitopes.…”
Section: Cell-mediated Xenograft Rejectionsupporting
confidence: 88%
“…Kits using multiplex technology, which are extremely useful for detection of large numbers of human and mouse cytokines in small sample volumes, does not exist with pig specificity. Unfortunately, a human multiplex kit tested in our laboratory showed very little cross-reactivity with porcine cytokines (174), and could therefore not be used in this Thesis.…”
Section: Pig In Vivo Modelmentioning
confidence: 99%
“…The upregulation was not inhibited by anti-CD14. In an ex vivo xenotransplantation model, upregulation of E-selectin was found to be highly and almost completely complement dependent (46). Furthermore, in an E. coli sepsis model in baboons, endothelial cell integrity was preserved by inhibition of complement (47).…”
Section: Discussionmentioning
confidence: 85%